2012
DOI: 10.3109/10428194.2012.720979
|View full text |Cite
|
Sign up to set email alerts
|

Fas-associated phosphatase 1 mediates Fas resistance in myeloid progenitor cells expressing the Bcr–abl oncogene

Abstract: The interferon consensus sequence binding protein (Icsbp) is a transcription factor that influences multiple aspects of myelopoiesis. Expression of Icsbp is decreased in the bone marrow of human subjects with chronic myeloid leukemia (CML), and studies in murine models suggest that Icsbp functions as an anti-oncogene for CML. We previously identified a set of Icsbp target genes that may contribute to this anti-oncogene effect. The set includes PTPN13, the gene encoding Fas-associated phosphatase 1 (Fap1, a Fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…We have found previously that increased expression of Fap1 and Gas2 in Bcr-abl ϩ myeloid progenitor cells, because of decreased Icsbp, resulted in Fas resistance and ␤-catenin activation (21)(22)(23)35). This study implicates the same pathways in sustained granulocyte production during emergency granulopoiesis in the absence of Icsbp.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…We have found previously that increased expression of Fap1 and Gas2 in Bcr-abl ϩ myeloid progenitor cells, because of decreased Icsbp, resulted in Fas resistance and ␤-catenin activation (21)(22)(23)35). This study implicates the same pathways in sustained granulocyte production during emergency granulopoiesis in the absence of Icsbp.…”
Section: Discussionsupporting
confidence: 58%
“…We found Fap1-dependent Fas resistance in Bcrabl ϩ and Icsbp Ϫ/Ϫ bone marrow progenitors (21,23). Fap1 also interacts with adenomatous polyposis coli protein, facilitating Gsk3␤ inactivation (dephosphorylation) by Fap1 (35).…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Fas resistance in CML is not due to decreased Fas or Fas ligand, but our studies suggested a role for Fas inhibition by Fas-associated phosphatase 1 (Fap1). 13–16 During progression to blast crisis (BC), β-catenin activity increases, expanding the LSC pool. 14,17 Increased β-catenin activity in CML is not due to altered Wnt or Wnt receptors, but our studies implicated glycogen synthase kinase-3β (Gsk3β) inhibition by Fap1.…”
Section: Introductionmentioning
confidence: 99%